IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN BAHASA INDONESIA DI SMPN 1 RANGKASBITUNG: TANTANGAN DAN PELUANG - Prasasti Dwi Putri; Vira Maulani; Tatu Hilaliyah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study examines the implementation of the Kurikulum Merdeka (Freedom Curriculum) at SMP Negeri 1 Rangkasbitung, Banten, as part of Indonesia's educational reform to meet the demands of globalization. The Kurikulum Merdeka is designed to offer flexibility, enabling project-based learning, instilling character values, and focusing on essential competencies for students. The findings reveal significant changes in teaching methods and evaluation approaches. However, challenges have been identified, including difficulties in adaptation by both teachers and students, limited supporting facilities, and insufficient involvement of key stakeholders. Efforts to address these challenges involve strategies such as intensive teacher training, strengthening school operational support, enhancing parental engagement, and leveraging technology to support learning. The study highlights the positive impact of the curriculum on increasing student engagement, personalizing the learning process, and fostering 21st-century skills, such as critical thinking, collaboration, and creativity. Data were collected through in-depth interviews with teachers, principals, and students, as well as direct classroom observations and analysis of documents related to the curriculum. Thematic analysis was employed to identify patterns of implementation, challenges encountered, and strategies adopted. Triangulation of data sources and methods ensured the validity of findings. The results underscore the potential of the Kurikulum Merdeka to enhance educational quality when supported by adequate resources and stakeholder collaboration. This research serves as a reference for other schools in adopting the curriculum effectively, promoting meaningful and future-oriented education for students.